2021
DOI: 10.3390/app11115200
|View full text |Cite
|
Sign up to set email alerts
|

kf Evaluation in GFRP Composites by Thermography

Abstract: Since the presence of a notch in a mechanical component causes a reduction in the fatigue strength, it is important to know the kf value for a given notch geometry and material. This parameter is fundamental in the fatigue design of aeronautical components that are mainly made of composites. kf is available in the literature for numerous types of notch but only for traditional materials such as metals. This paper presents a new practice, based on thermographic data, for the determination of the fatigue notch c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The thermal signature of fatigue-loaded (R= 0.1) CFRP samples due to notch-induced stress concentration have been captured and on mapping the temperature rise of hot zones offers a quicker way to determine the fatigue limit by NDT [31]. A similar trend of rising in temperature was recorded with in-situ impact-loaded composite thus substantiating the occurrence of damage on the structure [32] [33].…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…The thermal signature of fatigue-loaded (R= 0.1) CFRP samples due to notch-induced stress concentration have been captured and on mapping the temperature rise of hot zones offers a quicker way to determine the fatigue limit by NDT [31]. A similar trend of rising in temperature was recorded with in-situ impact-loaded composite thus substantiating the occurrence of damage on the structure [32] [33].…”
Section: Introductionmentioning
confidence: 60%
“…32 Such thermal signatures have been captured and mapped with various zones of the specimen to facilitate easy identification of fatigue limit and the corresponding damage. 30,33,34…”
Section: Introductionmentioning
confidence: 99%
“…An edge notch was applied to both edges of the sample to initiate the stress concentration. The results concluded that the technique can be efficiently used and improved by considering temperature adjustment [ 21 ]. Another study by Colombo et al [ 22 ] incorporated simulation analysis using delamination crack propagation using cohesive elements to strengthen the data during the GFRP laminate testing that used thermographic equipment.…”
Section: Introductionmentioning
confidence: 99%